2020
DOI: 10.1063/5.0005487
|View full text |Cite
|
Sign up to set email alerts
|

Localized surface plasmon-induced vibrational excitations in the surface-enhanced Raman scattering using two-dimensional array of silver nanocubes

Abstract: We have investigated the nanoscale structural and vibrational properties of polyvinylpyrrolidone (PVP)-covered silver nanocubes (AgNCs) array. The ordered AgNCs array fabricated on Au(111) by the Langmuir–Blodgett method was utilized for a surface-enhanced Raman scattering (SERS) platform. The local arrangements and the facet structure of AgNCs were observed by various types of microscopies, which revealed that AgNCs form an ordered monolayer and exhibit an atomically flat facet. The vibrational peaks associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…The height analysis indicated that the root mean square (rms) roughness of the AgNC surface is 0.32 nm. This means that the facets of AgNC are almost atomically at, as was pointed out in a previous paper 27. Fig.3(a) shows the Raman spectrum of PVPcovered AgNCs/Au(111) at room temperature.…”
supporting
confidence: 63%
See 4 more Smart Citations
“…The height analysis indicated that the root mean square (rms) roughness of the AgNC surface is 0.32 nm. This means that the facets of AgNC are almost atomically at, as was pointed out in a previous paper 27. Fig.3(a) shows the Raman spectrum of PVPcovered AgNCs/Au(111) at room temperature.…”
supporting
confidence: 63%
“…The Au(111) substrate was obtained by evaporating Au (purity, 99.99%) on a freshly cleaved mica surface under vacuum (3 Â 10 À4 Pa), followed by annealing at 500 C. [41][42][43] The 2D array of AgNCs was fabricated on Au(111) by the LB method. 27 We evaluated the shape and array structures of AgNCs by SEM (Hitachi High-tech, SU8000) and AFM (SII, SPI3700, contact mode). Raman spectroscopy (JASCO, NRS5100) was performed at room temperature under an atmosphersic condition using a laser of 532 nm wavelength (spot diameter, 1 mm, power, 0.01 mW), a 600 lines per mm diffraction grating, and a Â100 objective (N.A.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 3 more Smart Citations